Non-Tariff Protectionism – New Stage (Economic and Political Thought, 2013)
The analysis of non-tariff protectionism presented in the article in thecontext of its reasons, forms and influence on international trade results ina conclusion that we deal with a phenomenon that has immanently becomepart of the mechanism of global economy; both in the context of its structuralform and opportunistic manifestations of activeness. Rather paradoxically,the countries that have achieved a high level of economic development try toprotect their financial status with the use of NTM. Non-tariff protectionismdemonstrates its restrictive form especially in the periods of crisis and hitsthe weaker links of international exchange – less developed countries. Thechangeable form of contemporary protectionism measures, often defined asa ‘moving target’, makes liberalization activities more difficult. They are moreand more complex in the light of changes that are taking place in the contemporaryworld due to a more and more dynamic scientific and technologicalprogress. That is why TBT/SPS have become so important in the whole rangeof non-tariff measures and difficulties with curbing their restrictive influenceoccur. Undoubtedly, it is necessary to increase efforts in order to awakenthe conscience about threats resulting from the selfish use of NTM in internationalexchange and look for effective ways of fighting against non-tariffrestrictions. It can be assumed that the efforts on the arena of the WTO andother international organizations that aim at the above-mentioned principleswill reach an adequate critical mass necessary to start liberalization activitiesin international trade in the predictable future.